Boosting the photocatalytic activity of ZnO-NPs through the incorporation of C-dot and preparation of nanocomposite materials - Asegid Belete Tegenaw; Ahmed Awol Yimer; Tamene Tadesse Beyene (Heliyon, 2023)
Due to their applications in cosmetology, medicine, antibacterial and other fields, zinc oxide nanoparticles (ZnO-NPs) are among the nanoscale materials experiencing exponential growth. In contrast, pure ZnO-NPs have been reported to have a very large energy bandgap, a large exaction binding energy, electron-hole recombination, no visible light absorption, and poor photocatalytic activities, which limit their potential uses. ZnO-NPs can be further extended through the incorporation of trace amounts of carbon materials to engulf these problems. We investigate the photocatalytic degradation of methylene blue (MB) dye with pure ZnO-NPs infused with a limited amount of carbon dot (C-dot) materials. Consequently, adding 10% C-dot to ZnO-NPs reduced their energy bandgap from 3.1 to 2.8 eV and significantly increased their photocatalytic activity. MB was almost completely degraded (98.4%) after 60 min when 50 mg of C-dot-incorporated ZnO-NPs were added. By comparison, the nanocomposite's photocatalytic activity exceeded that of pure ZnO-NPs by more than 50%. A surface charge and stability improvement are responsible for the extraordinary photocatalytic improvement. As far as we know, this is the best-ever photocatalytic improvement achieved by incorporating a trace amount of C-dot material into pure ZnO-NPs.